2011
DOI: 10.4049/jimmunol.1100002
|View full text |Cite
|
Sign up to set email alerts
|

Loss of T Cell CD98 H Chain Specifically Ablates T Cell Clonal Expansion and Protects from Autoimmunity

Abstract: CD98hc (CD98 heavy chain, 4F2 antigen, Slc3a2) was discovered as a lymphocyte activation antigen. Deletion of CD98hc in B cells leads to complete failure of B cell proliferation, plasma cell formation, and antibody secretion. Here we examined the role of T cell CD98 in cell-mediated immunity and autoimmune disease pathogenesis by specifically deleting it in murine T cells. Deletion of T cell CD98 prevented experimental autoimmune diabetes associated with dramatically reduced T cell clonal expansion. Neverthele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
86
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 54 publications
5
86
0
Order By: Relevance
“…A previous study using CD98hc-deficient T cells showed reduced T cell proliferation, but no defect in acquiring effector functions (16). This article indicated that defective T cell proliferation in CD98hc-deficient T cells is attributed to lack of the integrin-binding domain of CD98hc (16). Therefore, the suppressive effect of I-142 on T cell effector functions in our studies might suggest that the I-142 mAb influences other functions of CD98hc besides integrin activity.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…A previous study using CD98hc-deficient T cells showed reduced T cell proliferation, but no defect in acquiring effector functions (16). This article indicated that defective T cell proliferation in CD98hc-deficient T cells is attributed to lack of the integrin-binding domain of CD98hc (16). Therefore, the suppressive effect of I-142 on T cell effector functions in our studies might suggest that the I-142 mAb influences other functions of CD98hc besides integrin activity.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, our anti-CD98hc mAb was able to suppress Ag-specific proliferation and effector functions of both CD4 + and CD8 + T cells in vitro and in vivo. A previous study using CD98hc-deficient T cells showed reduced T cell proliferation, but no defect in acquiring effector functions (16). This article indicated that defective T cell proliferation in CD98hc-deficient T cells is attributed to lack of the integrin-binding domain of CD98hc (16).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Rapid proliferation of other cell types such as T cells 21 and B cells 12 is dependent on CD98hc. We show in vivo that after 8 weeks of HFD, CD98hc −/− VSMC display significantly reduced proliferation and increased apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 99%